Life Cycle Assessment of multiyear peach production. (1st October 2015) - Vinyes, Elisabet; Gasol, Carles M.; Asin, Luis; Alegre, Simó; Muñoz, Pere
Abstract: Considering that peach is a significant fruit in the Mediterranean countries, and most publications on environmental impacts of fruit productions are based on one single productive year, this study attempts to perform an environmental analysis of peach production using Life Cycle Assessment, in order to provide new information on peaches, and also introduce a multiyear perspective analysis to identify the variability of the environmental impacts related to annual orchard yield and weather variations. The system studied is a peach orchard ( Prunus persica L. ) with integrated agricultural practices. The study analyses the cultivation period, as well as the impact of the initial orchard establishment tasks (soil preparation and planting). Data used have been collected directly from an orchard located in the North East of Spain, and covers 15 years of real production. The functional unit adopted was the cultivation of 1 kg of peach. Four scenarios have been considered according to the different yield periods of the peach fruit tree: Growth, Low, High and Multiyear . The results of the study reveals that, depending on production scenario considered, the results per kg of peach can vary between 7% and 69% depending on the environmental indicator. If the impact of initial orchard establishment tasks (soil preparation and planting) is not included in the quantification, then 5% of total emissions may be overlooked, but sometimes a lack of data makes it difficult to include these stages. Caution should be taken when the functional unit is related to mass and only when a single year of production is studied, because unproductive years increase impacts on value per functional unit, whereas over-productive years decrease them. According to variability of the results obtained, multiyear approach should be considered in crops with an average life time of twenty years or higher. The present study can be considered a useful methodological framework for providing a deeper understanding of the key environmental impact issues related to fruit production based on peach case study, and how to avoid multiple interpretation of results associated to reporting annual environmental impact variations. Highlights: This work is based on multiyear perspective analysis. It includes the impact of the initial orchard establishment tasks. It analyses the variability of the environmental impacts related to annual orchard yield. Data used were collected directly from a real orchard.